Persistent Coronary Vasomotor Tone During Myocardial Ischemia Occurs at the Capillary Level and May Involve Pericytes - Le, D. Elizabeth; Zhao, Yan; Kaul, Sanjiv (Frontiers in Cardiovascular Medicine, 2022)
Background: There is persistent coronary vasomotor tone during myocardial ischemia despite ongoing coronary arteriolar dilatation. The mechanism underlying this vasodilatory reserve, which can be unmasked by coronary vasodilators, is unclear. We hypothesized that persistent microvascular resistance during myocardial ischemia occurs at the level of capillaries and may be caused by pericyte contraction. Methods: We studied nine instrumented dogs where coronary blood flow and coronary driving pressure were reduced to half by placement of stenoses. Myocardial blood flow and myocardial blood volume were measured with myocardial contrast echocardiography before and during adenosine administration. In 3 animals, the heart was perfusion fixed under these conditions for electron microscopic assessment of capillary and pericyte size. Results: During ischemia, myocardial blood volume decreased and myocardial vascular resistance remained unchanged despite ongoing autoregulation. Adenosine administration reversed the decline in myocardial blood volume and decreased myocardial vascular resistance. Electron microscopy showed larger capillaries in ischemic beds receiving adenosine compared to ischemic beds not receiving adenosine. Pericytes in beds receiving adenosine also tended to be larger. Conclusions: Capillaries are the site of persistent microvascular tone during myocardial ischemia; any other site of vascular regulation (arterioles or venules) cannot explain these findings, which are confirmed on post-mortem electron microscopic examination. Since capillaries have no smooth muscle, the decrease in capillary size is likely caused by pericyte contraction in an attempt to maintain a constant capillary hydrostatic pressure. Adenosine relaxes pericytes, restores myocardial blood volume, reduces myocardial vascular resistance, and improves regional function during ischemia. These findings could have important therapeutic applications.